APLlKASI AL-MUZARA 'AH DI FELCRA BERHAD - Mohd Shafiai, Muhammad Hakimi (Jurnal Syariah, 2019)
This paper analyzes the cooperation between FELCRA Berhad a developer of agricultural land owners based on the principles of almuziira 'ah. These principles are cooperative contract between the land developer and the owner of land to develop the land. In order to achieve the objective, the researcher conducted both library research and field work. Library research was used to get data related to the principles ofjiqh on al-muziira 'ah. Field work was carried out based on two instruments namely. interviews and questionnaires. Interview sessions were carried out with the FELCRA Berhad ofSeberang Perak representatives as the agricultural of instrumentations land developer. Questionnaires were distributed to the participants who were the owners of the land. Based on two methods, the researcher found that the activities carried out in the development of agricultural land in Seberang Pertik fulfiled most of the basic principles of al-muziira 'ah. This includes the terms of contract, cooperation, agreement and distribution of yield between the land developer and the land owner.